Influence of static mixer on the formation of biogranules - Suryati, Sulaiman; Azmi, Aris; Abdul Syukor, Abd Razak; Khalida, Muda; Aznah, Nor Anuar (Penerbit Universiti Teknologi Malaysia, 2019)
Present study aimed at evaluating the formation of biogranules using sequencing batch reactors (SBRs) in treating textile wastewater under the influence of static mixer. Three sets of experiment were run with different superficial air velocity (SAV) of 0.5, 1.4 and 2.1 cms-1, each set consisting of two SBR one with and one without static mixer. The developed biogranules in reactors with static mixer (R1M, R2M and R3M) showed good results after approximately 70 days. The biomass in the reactor reached mix liquor suspended solid (MLSS) of 5.75 gL-1 with sludge volume index (SVI) of 107.4 mLg-1 and settling velocity (SV) of 70.3 mh-1 in R1M; MLSS of 7.18 gL-1 with SVI of 29.5 mLg-1 and SV of 80.4 mh-1 for R2M and MLSS of 7.38 gL-1 with SVI of 36.3 mLg-1 and SV of 74.2 mh-1 for R3M. The use of static mixer has contributed to biogranules development with good settling properties.